CARACTERIZAÇÃO DA PESCA DE PEQUENA ESCALA DO FAROL DE SANTA MARTA, LITORAL SUL DE SANTA CATARINA: Characterization of the small-scale fishing fleet at Farol de Santa Marta, southern coast of Santa Catarina - Ramos Arrial, Luiz Gustavo; Volkmer de Castilho, Pedro; Domit, Camila; Pacheco Bertozzi, Carolina; Gama Vidal, Lara; Machado, Rodrigo (Arquivos de Ciências do Mar, 2024)
Farol de Santa Marta (FSM) is a traditional fishing community in the state of Santa Catarina (SC). Fishing at FSM is an activity with great cultural and socioeconomic importance. Despite the importance, the lack of information regarding fishing activities is flagrant. In this sense, the present study aimed to characterize the small-scale fishing activity at Farol de Santa Marta. The FSM fishing fleet was characterized by the masters of 26 vessels using the “snowball” method. As a result, we identified that the main fishing gear used were surface and bottom-set gillnets and surrounding nets. The main target species are the bluefish (Pomatomus saltatrix) and the mullet (Mugil liza). The most commonly used vessels at FSM were the small boats. The fishing areas explored by the fleet were limited to the south by the city of Passo de Torres - SC and to the north by Florianópolis - SC. The commercialization of fish is carried out by middlemen and the profits between the fishermen of the FSM are divided in parts. Although it has changed over time, the small-scale fishing of Farol de Santa Marta is still the community's main source of local income, generating earnings and food for countless families. Keywords: Ethnobiology. Traditional knowledge. Artisanal fishing. Socioeconomics. Regional development.